Statistical Analysis Plan for the Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package in INDIA (SPRINT INDIA): A Randomized Controlled Trial. Issue 1 (June 2022) - Khatter, Himani; Pandian, Jeyaraj D.; Kate, Mahesh; Sarma, Sankara; Sylaja, PN; Khurana, Dheeraj; Vijaya, Pamidimukkala; Ray, Biman Kanti; Nambiar, Vivek; Aaron, Sanjith; George, Tina; Mittal, Gaurav; et al.
Background: Recurrent stroke is one of the major causes of death in stroke patients. Introducing stroke prevention education package to improve the lifestyle behavioral factors could reduce the vascular events. The Secondary Prevention by Structured Semi-Interactive Stroke Prevention Package (SPRINT) study in India aims to assess the role of a stroke prevention education package to reduce recurrent strokes, myocardial infarction, and death in patients with stroke. The objective is to formulate the detailed statistical analysis plan for the SPRINT India prior to trial unblinding. Methods: The plan was developed by trial statisticians with the help of principal investigator and management team of the SPRINT study. The chosen primary and secondary outcome measures and knowledge of critical baseline data were used to construct the statistical analysis plan. All collected data will be thoroughly reviewed. Patient baseline characteristics will be summarized with relevant descriptive statistics. The findings are planned and explained for the most appropriate statistical comparison between the groups. Results: The final statistical analysis plan corresponds to established criteria and will allow for transparent and efficient reporting. Conclusions: The SPRINT trial statistical analysis plan is developed in order to avoid analysis bias arising from prior knowledge of findings and to explicitly summarize prespecified analyses.